AIR ACCUMULATING ELECTRIC POWER STATION WITH TWO AIRSTORAGE RESERVOIRS OF DIFFERENT PRESSURE - Mokin, Boris; Chepurnyj, Marko; Mokin, Oleksandr (Scientific Works of Vinnytsia National Technical University, 2015)
There had been suggested the structure of air accumulating electric power station with two air-storage reservoirs of different pressure connected to each other by the compressor-gas-expansion machine. There had been determined the basic characteristics of this class of power stations and design procedure of this characteristics.